Effect of tempering conditions on dynamic deformation behaviour of an aluminium–lithium alloy. (15th September 2015) - Ghosh, A.; Adesola, A.; Szpunar, J.A.; Odeshi, A.G.; Gurao, N.P.
Graphical abstract: Highlights: Tempering condition affects dynamic deformation of Al–Li alloy. Presence of 〈1 0 1〉 component in compression direction and shear bands in all samples. Extended dislocation–precipitate interaction for underaged T4 sample. Single step peak aged sample exhibits high toughness with stable microstructure. Abstract: The deformation behaviour of an aluminium–lithium alloy heat treated to different tempering conditions was investigated at high strain rate in compression using a direct impact Hopkinson Pressure bar. Detailed microstructural investigation was carried out using electron back scatter diffraction and bulk crystallographic texture was determined using X-ray diffraction. All the impacted samples showed presence of adiabatic shear bands irrespective of the prior ageing condition, however, the extent of grain fragmentation and strength of 〈1 0 1〉 parallel to compression direction texture component was strongly dependent on the tempering condition of the alloy. The naturally aged sample showed less propensity to adiabatic shear band formation and therefore, highest toughness, compared to artificially aged samples. This can be attributed to higher resistance to instability by prolonged strain hardening from dislocation–precipitate interaction in the underaged sample compared to peak and over aged samples under dynamic loading conditions. The single stage peak-aged sample provides the best combination of high toughness with stable microstructure amongst the differently aged samples.